Modeling and characterization of Schottky diode on AlGaAs/GaAs HEMT structure for rectenna device - Parimon, Norfarariyanti; Mohd. Yusof, Siti Suhaila; Hashim, Abdul Manaf (2008)
The modeling and characterization of Schottky diode on AlGaAs/GaAs HEMT structure for rectenna device is presented. The rectenna device can be used as a wireless power supply where it can capture microwave power and convert to the dc power to generate the others devices or circuits on a chip. Design and simulation of Schottky diode on AlGaAs/GaAs HEMT structure was carried out. From the simulated results, it was found that the operating frequency of the Schottky diode is tunable based on the length ofcoplanar waveguide.